Right-to-know on risks from exposure to building materials during refurbishment of heritage mosques / Muhammad Zahir Zulkernain, Muhamad Ferdhaus Sazali and Nurhidayah Samsul Rijal - Zulkernain, Muhammad Zahir; Sazali, Muhamad Ferdhaus; Samsul Rijal, Nurhidayah (2022)
Refurbishment work is more complicated than new projects because it involves dismantling, demolition, removal, and new installation. The jobs apply to different stakeholders and the public within the vicinity of the projects or using the spaces such as in a Masjid (Mosque). The stakeholders are vulnerable to health and safety risks exposure due to unknown risks and limited information about the project. Scientific findings showed that human health and safety are at risk of being exposed to dust, fumes, gases, vapours, and toxic building materials. There are potential hazards due to an accident that causes harm or adversely affects the health and safety of the stakeholders. This paper discusses the potential risks to health and safety from building materials for future heritage mosques refurbishment projects. Visible observations were selected as the research method and were carried out on three sites that are listed as heritage mosques in Klang, Selangor. Hazardous materials will be identified from the inspections. Findings revealed that there are potential risk exposures due to materials, construction, and the working environment. Hence, there is a need to consider risk management before any refurbishment works. The findings should be informed to the stakeholders as they have the right to know.